Fabrikasi Alat Pelontar Bola Takraw - Mohd Naim, Sapie (UTeM, 2008)
Bachelor project appertain takraw ball ejector machine is the project to make the training of takraw game more systematic for takraw trainer. This project conduct the performance analysis of takraw ball ejector for the training of takraw game. The ball launcher based on experimental data of takraw ball flight angles, velocity, and distance travelled in the game match. In takraw training, human energy still used for launch balls to trainer. The accuracy of ball movement to the trainer not so good. The machine should suitable to the system and rules in takraw game. This ejector machine can be managed to regulate the ball movement.